Stalked crinoids (Echinodermata) collected by the R/V Polarstern and Meteor in the south Atlantic and in Antarctica - Eléaume, Marc; Bohn, Jens-Michael; Roux, Michel; Améziane, Nadia (Zootaxa, 2012)
During the last decades, R/V Meteor and R/V Polarstern deep-sea investigations in the south Atlantic and neighbouringSouthern Ocean collected new samples of stalked crinoids belonging to the families Bathycrinidae, Phrynocrinidae andHyocrinidae which are herein described. The species found are Bathycrinus australis A.H. Clark, 1907b (the most abun-dant), Dumetocrinus aff. antarcticus (Bather, 1908), Hyocrinus bethellianus Thomson, 1876, Feracrinus heinzelleri newspecies, and Porphyrocrinus cf. incrassatus (Gislén, 1933). As only stalk fragments of bathycrinids were frequently col-lected, a distinction between the two Atlantic species B. australis and B. aldrichianus is proposed using characters of co-lumnal articulations. A few specimens attributed to Porphyrocrinus cf. incrassatus, Hyocrinus bethellianus and Hyocrinussp. collected by the N/O Jean Charcot on the Walvis Ridge are also described, plus a new specimen of Porphyrocrinusincrassatus collected in the central mid-Atlantic. Biogeography and close affinities between species in the genera Bathy-crinus and Porphyrocrinus suggest an Antarctic origin of some stalked crinoids among the north Atlantic deep-sea fauna.The presence of B. australis in both the Angola and Cape basins suggests that the Walvis Ridge is not a bio-geographicalbarrier for this relatively eurybathic species, which can attach to hard substrates as well as anchor in sediment. The genusDumetocrinus seems to be an example of colonization of the west Antarctic platform from deeper environment where its ancestor lived.